Improvement of Ukraine’s Legislation on Food Security in the Context of European Integration - Volchenko, Nataliia (Research Papers, 2018)
Food security of the state is a component of national security. Satisfaction of the population with food forms the basis for realization of all further possibilities of state’s development. Ukraine, being on the path of active realization of European integration aspirations, should pay particular attention to such issues.The originality of the article is proved by the fact that it is prepared in the frames of the project for the young scientists of Ukraine of 2017.